KEPALA SEKOLAH SEBAGAI PEMIMPIN DAN PENDIDIK DI SEKOLAH DASAR - Sutrisno Sutrisno (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
The purpose of this study was to obtain information about the management of school principals' duties as leaders and as teachers in elementary schools in 29 Public Elementary Schools in Rimau Island, Banyuasin District. This study uses a qualitative approach that emphasizes more meaning than generalization. The research subjects consisted of 1 principal, 4 teachers and 1 administrative staff member. Data is obtained by means of interviews, observations, and documents. In analyzing the data using 3 activity lines, namely data reduction, data presentation, and verification. The results of data analysis show; (1) The management of the principal's job as a teacher in Elementary School 29 Pulau Rimau has been well implemented, especially in managing the time to carry out academic assignments as a teacher by selecting teaching days which are considered not too many school principals' activities Friday and Saturday; (2) Management of school principals' tasks as leaders carried out by the principal of the Elementary School 29 Pulau Rimau includes the transformation of Vision and Mission by carrying out management functions in the management of school resources (facilities, infrastructure, teachers and staff).